Globalization: its complexity and critique – on the need to direct the society towards knowledge - Cybal-Michalska, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2023)
Contemporary discourse on the quality of a globalising world of multiple opportunities, the factors determining shifts in the social configuration and the condition of the human being seeking their place in a reality in constant changeis one of the most important orientations. The contemporary social configuration opens up a wide range ofpossibilities for individuals to construct their own biographies. Contemporary studies on the quality of the globalizing society necessitate considering the need to shape society based on knowledge and reflection on that knowledge,while also guarding the values upon which this knowledge depends. The immanent characteristic of the renewal of knowledge capital means continuous development. The variety, fragmentation, variability and complexity of the forms of organisation of social life in a globalising society determine changing perceptions of development and overcoming the tension between the experiences of the past and the possibilities of the future.